PENDIDIKAN KARAKTER PERSPEKTIF AL-QUR’AN SEBAGAI SYIFA’UL QULUB - Nafisah, Nisa'atun (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
Currently, various character problems are increasingly worrying. Moral degradation is a serious problem and the fading of religious and moral values in society requires special attention in the realm of education. Strengthening character education is a priority program for the Indonesian government in reforming the national education system. One of the good qualities that a person needs to have is humility. Humility will bring about a good relationship between humans and Allah SWT (habluminallah) as well as relationships between humans (habluminannas). The side of the miracles of the Al-Qur'an should be emulated again by humans, so that humans remember that their arrogance in all the advantages they have will be incomparable with the miracles of the Al-Qur'an. To minimize arrogance, it is necessary to develop the concept of character education based on the Qur'an as Syifa'ul Qulub, so that in the future it can become the basis for developing practical and applicable character education. This study uses a qualitative approach. The method used in this study is the reference search method or literature study. The results of this study show that the Qur'an as a human guideline provides guidance to avoid heart disease and provides a way out when the human heart has been damaged because of arrogance. Internalization of the values of the Qur'an in shaping character education through the function of the Qur'an as syifa'ul qulub. The ultimate goal of character education is to form a child's personality who has noble morals as the morals of the Prophet Muhammad. Abstrak Karakter menjadi permasalahan yang semakin serius untuk diperhatikan. Sebab semakin banyaknya degradasi moral yang menyebabkan lunturnya nilai-nilai agama serta susila di masyarakat sehingga perlu mendapatkan perhatian khususnya pada ranah dunia pendidikan. Penguatan pendidikan karakter menjadi program prioritas pemerintah Indonesia dalam membenahi sistem pendidikan nasional. Salah satu sifat baik yang perlu dimiliki oleh seseorang adalah sifat rendah hati. Sifat rendah hati akan memunculkan hubungan baik antara manusia dengan Allah Swt (habluminallah) serta hubungan antara sesama manusia (habluminannas). Sisi kemukjizatan Al-Qur’an patut kembali diteladani oleh manusia, agar manusia ingat bahwa kesombongannya dalam segala kelebihan yang dimiliki tidak akan ada bandingnya dengan kemukjizatan Al-Qur’an. Untuk meminimalisir sifat sombong, maka perlu disusun konsep pendidikan karakter berdasarkan Al-Qur’an sebagai Syifa’ul Qulub, sehingga ke depan bisa menjadi dasar pengembangan pendidikan karakter secara praktis dan aplikatif. Penelitian ini menggunakan pendekatan kualitatif. Metode yang digunakan dalam penelitian ini adalah dengan metode penelusuran referensi atau studi literatur. Hasil penelitian ini menunjukkan Al-Qur’an sebagai pedoman umat manusia memberikan tuntunan agar terhindar dari penyakit hati dan memberikan jalan keluar tatkala hati manusia telah rusak karena kesombongan. Internalisasi nilai Al-Qur’an dalam membentuk pendidikan karakter melalui fungsi al-Qur’an sebagai syifa’ul qulub. Tujuan akhir dari pendidikan karakter adalah membentuk pribadi anak yang memiliki akhlak mulia sebagai mana akhlak Rasulullah SAW.